Nation branding through mega-events and the impact on tourism development in the host country: a study on the 2014 FIFA World Cup in Brazil - Sörensen, Mascha (2016)
Nation branding has recently gained importance as countries strive for a global competitive advantage to attract worldwide tourists, foreign direct investment and talented workforce, and to enhance consumer preferences for its exported products. The significance for Brazil of having hosted the two most important sport mega-events, the 2014 Football World Cup and the 2016 Summer Olympic Games, within two years is discussed in detail. The objective of the exploratory research here presented is to understand the perception of Brazil internationally (measured as nation brand) and to determine whether primarily the 2014 World Cup had an impact on the nation brand as possibly also on the tourism activities in the country. A methodology of a single case study has been applied. Main sources of information were secondary data from websites and tourism and event related journals, as well as quantitative data from nation branding indices and official tourism statistics. The most insightful data source was provided by seven interviews with experts in the field of nation branding, events and tourism business. The research suggests that the World Cup had two-sided effects. Increased international awareness, hospitality and improvements in perception of culture and people in Brazil are positive results that were partly restrained by negative images of corruption, insecurity and social problems. The World Cup overall resulted in positive outcomes in the tourism industry. Despite being beneficial in many aspects, the mega-events happened at a difficult economic and political time in Brazil. Together with persistent deficiencies of the international sport organizations, these circumstances further hindered lasting legacies and international reputation. The findings therefore are not straightforward. They are rather based on a complex discussion which identifies positive contributions of the events to destination branding and possibly to the development of the nation branding strategy of Brazil.